Laparoscopic Heminephrectomy for Duplex Kidney in Children—The Learning Curve - Polok, Marcin; Dzielendziak, Agata; Apoznanski, Wojciech; Patkowski, Dariusz (Frontiers in Pediatrics, 2019)
Objectives: Assessment of the efficacy of laparoscopic transperitoneal heminephrectomy in children with a duplex kidney. Material and Methods: The data of 33 children, operated between 2008 and 2017 with the diagnosis of complicated duplex kidney, were subjected to a retrospective analysis. All patients were operated on by transperitoneal access using the laparoscopic technique. Results: There was no need for conversion. Two patients (6%) required reoperation to remove the ureter stump because of recurrent UTI’s due to undiagnosed VUR to the stump. The prolonged urine leakage (over 4 days) was observed in 4 patients (12%), in 3 patients conservative treatment was successful, in 1 placing DJ catheter was needed. Significant decrease of the kidney function (>6%) in scintigraphy was observed in 2/15 patients after the surgery. Patients were divided into two groups to evaluate the learning curve. Most of complications occurred in group 1 (first 16 operations). Conclusions: Laparoscopic heminephrectomy is an effective surgical method in the treatment of the complicated duplex kidney. Due to the possibility of occurrence of undiagnosed reflux to the residual ureter stump, it is necessary to consider the removal of the ureter to the height of the vesicoureteral connection in all patients.